Estudio del perfil del turista local post covid-19, caso cantón Sigchos, provincia Cotopaxi. - Yugsi Almachi, Jessica Paulina (2021)
This research work was carried out in the Sigchos location, Cotopaxi province, due to the covid-19 pandemic, tourism has been stalled in its normal development also the emergency state in Ecuador keeps on the biosecurity measures active, it affects to providers service and local residents because they are not able to carry out the tourist attractions activities in location, therefore this study aims to establish the profile of the local tourist after covid-19, which was proposed to determine the preferences of the local tourist by applying data validation instruments that establish the visitor's profile. First, a questionnaire was designed to collect information taking into account the tourist profile variable. Then, information was collected by applying the instrument designed through on-site and / or virtual visits. Ending with the interpretation of the obtained information through the systematization and analysis of the respective variable and the determined conditions, which collaborated to define the profile of the local tourist with the help of the calculation program? The research type is descriptive since each step that was carried out in this study is described, and the applied methodology for the sample was the use of intentional non-probabilistic sampling, for this the respondents had to meet the two conditions to be the object of this study: being between 20 to 59 years of age; and, reside in the Sigchos city. As a result, the designed instrument by means of on-site visits and / or virtual visits to the inhabitants of the canton was applied on January 11th, 2021;The key questions to determine the profile of the local tourist were age: 31 to 39 years with 31%, they are single men, they like to share with the family with 34%, they visit cultural attractions with 41%, they visit destinations weekly Since they are independent people, this determines the reality of the local resident towards the new leisure and recreation activities that result from the pandemic. It is concluded that it is necessary to know ages, tastes, preferences, frequencies, spending capacity, activities to develop, and others facts, as it helps those involved in its management to make decisions in the tourism field and to plan sustainable development alternatives in the studying place, it means to have new forms of leisure and recreation activities as long as biosafety measures are applied, in order to promote the health of the local resident and the resources conservation.